2015
DOI: 10.1242/jeb.113704
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of muscle fibre input dynamics using amyog: GFP transgenic trout model

Abstract: The dramatic increase in myotomal muscle mass in teleosts appears to be related to their sustained ability to produce new fibres in the growing myotomal muscle. To describe muscle fibre input dynamics in trout (Oncorhynchus mykiss), we generated a stable transgenic line carrying green fluorescent protein (GFP) cDNA driven by the myogenin promoter. In this myog:GFP transgenic line, muscle cell recruitment is revealed by the appearance of fluorescent, small, nascent muscle fibres. The myog:GFP transgenic line di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…The persistence of myomaker expression in trout white muscle is associated with the persistence of new fiber formation from mosaic hyperplasia. Accordingly, the lowest expression of myomaker was observed in mature fish, when hyperplasia is reduced (20,28).…”
Section: Insertion Of Minisatellites In Trout Myomaker Proteinmentioning
confidence: 94%
“…The persistence of myomaker expression in trout white muscle is associated with the persistence of new fiber formation from mosaic hyperplasia. Accordingly, the lowest expression of myomaker was observed in mature fish, when hyperplasia is reduced (20,28).…”
Section: Insertion Of Minisatellites In Trout Myomaker Proteinmentioning
confidence: 94%
“…At post-larval stages, new myofibres are formed between existing muscle fibres throughout the myotome, thus producing a typical mosaic appearance in muscle cross sections [2]. A Myog:GFP transgenic trout model has revealed that mosaic hyperplasia is prevalent in the juvenile stage, but progressively decreases as trout age, and eventually ceases at approximately 18 months post-fertilization [7]. Nevertheless, potentially recruitable muscle stem cells are present in muscles of aged trout, as shown by their ability to form myofibres de novo after muscle injury [7, 8].…”
Section: Introductionmentioning
confidence: 99%
“…Genes belonging to this functional category included genes encoding cell division cycle (cdc) 84 proteins (8), cyclin dependent kinases (6), cyclins (6), genes involved in chromosomes segregation 85 (20) as shown in figure 3. Enrichment in gene involved in DNA metabolic process and replication 86 such as minichromosome maintenance complex components, non-homologous end-joining factor1, 87 DNA polymerases, DNA primases, DNA topoisomerases, replication proteins were also found.…”
Section: Myogenic Precursors Extracted From Hyperplasic and Non-hypermentioning
confidence: 99%
“…The second process 31 refers to the formation of new muscle fibers throughout the entire myotome and is termed 32 hyperplasia [1][2][3]. A persistence of hyperplasic growth after juvenile stage was reported in large 33 final size fish as gilthead bream [4], carp [5], european sea bass [6] and rainbow trout [7,8]. 34 Nevertheless, this production of new muscle fibers decreases with age [7], and hyperplasia was no 35 longer observed in 18-months old trout [8].…”
mentioning
confidence: 99%
See 1 more Smart Citation